The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12903-021-01495-2
|View full text |Cite
|
Sign up to set email alerts
|

Facial alveolar bone thickness and modifying factors of anterior maxillary teeth: a systematic review and meta-analysis of cone-beam computed tomography studies

Abstract: Background Understanding the anatomy of the facial alveolar bone (FAB), provides a prognostic tool for estimating the degree of dimensional ridge alterations after tooth extraction. This systematic review and meta-analysis aims to determine the FAB thickness and modifying factors of anterior maxillary teeth measured by CBCT scans. A secondary objective was to assess the facial distance from the cementoenamel junction (CEJ) to the bone crest. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…A systematic review showed that geographic environment was an effective modifier that explained the reason for up to 87% of alveolar bone thickness heterogeneity. Asians have thinner anterior alveolar bones than Europeans ( 22 ). The thinner alveolar bones of Asian populations made the difference between these three groups not detectable.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review showed that geographic environment was an effective modifier that explained the reason for up to 87% of alveolar bone thickness heterogeneity. Asians have thinner anterior alveolar bones than Europeans ( 22 ). The thinner alveolar bones of Asian populations made the difference between these three groups not detectable.…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative state was compared with the immediate postoperative condition, and the outcome after year, both overall and compared with taking the graft and/or SST. Since the thickness of the peri-implant tissues varies throughout the vertical axis [ 30 , 31 ], measurements were taken at 3, 5, and 7 mm from the gingival margin. The implant platform was used as a reference point measuring changes in alveolar crest height.…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar resorption occurs more markedly in a horizontal dimension, followed by vertical changes in medial buccal and medial lingual areas. Buccal cortical thickness is related to the degree of resorption after tooth extraction, the greater thickness being a protective factor for bone remodeling [ 30 , 40 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone thickness of 1.8-2 mm on the buccal aspect of dental implants has been suggested to ensure predictable long-term stability of the hard and soft tissues. 44,47 However, according to several studies, [48][49][50] the reported buccal bone thickness in the maxillary anterior region-as measured by computed tomography in healthy patients-is frequently less than 1 mm in as many as 74% of cases. In addition, as a consequence of postextraction alveolar remodeling, the mean changes in horizontal bone dimensions at immediate implant sites in the maxillary esthetic zone amount to nearly 0.7 mm.…”
Section: Bone Aug Mentationmentioning
confidence: 99%